Open supply? On the future of document supply in the world of open science. Issue 4 (21st November 2016) - Schöpfel, Joachim
Abstract : Purpose: The purpose of this paper is to propose a personal viewpoint on the development of document supply in the context of the recent European Union (EU) decisions on open science. Design/methodology/approach: The paper provides some elements to the usual questions of service development, about business, customers, added value, environment and objectives. Findings: The EU goal for open science is 100 per cent available research results in 2020. To meet the challenge, document supply must change, include more and other content, serve different targets groups, apply innovative technology and provide knowledge. If not, document supply will become a marginalized library service. Originality/value: Basically, open science is not library-friendly, and it does not offer a solution for the actual problems of document supply. But it may provide an opportunity for document supply to become a modern service able to deal with new forms of unequal access and digital divide.